(untitled) (Società e diritti, 2025)
il In contemporary society, youth violence is undergoing a profound cultural redefinition, oscillating between normalization and trivialization. Normalization occurs as society becomes increasingly desensitized to violent behaviours, integrating them into everyday life and diminishing their disruptive nature, thus reducing individual accountability. Trivialization, on the other hand, arises when violence is no longer perceived as exceptional but rather as entertainment, performance, or a tool for social validation, particularly within digital and media environments. This study explores this dual process, highlighting how continuous exposure to violence reshapes collective perception, gradually erasing its sense of severity and urgency. In a landscape where violence is not only enacted but also consumed and symbolically reproduced, the greatest risk lies in its full assimilation into social dynamics, stripping it of ethical and critical reflection.